Tight Blood Glucose Control Is Renoprotective in Critically Ill Patients - Schetz, Miet (American Society of Nephrology, 2008)
Two large, prospective, randomized, controlled trials have shown a beneficial effect of intensive insulin therapy (IIT) on the kidney function of critically ill patients. The data from these trials were combined for performance of a more detailed analysis of the renoprotective effect of IIT. After exclusion of 41 patients with preadmission ESRD, the study sample comprised 2707 critically ill patients who were randomly assigned to conventional or IIT. A modified risk-injury-failure-loss-ESRD (mRIFLE) system was used to classify acute kidney injury such that mRIFLE-Injury and -Failure (mR-IF) corresponded to peak serum creatinine levels ≥2× and ≥3× the admission levels, respectively. IIT significantly reduced the incidence of mR-I or -F from 7.6 to 4.5% (P = 0.0006), and this renoprotective effect was most pronounced in patients who achieved strict normoglycemia. In surgical patients, IIT also significantly reduced oliguria (from 5.6 to 2.6%; P = 0.004) and the need for renal replacement therapy (from 7.4 to 4.0%; P = 0.008). In medical patients, the incidence of mR-I or -F decreased to a lesser extent, perhaps because a greater severity of illness at admission may have rendered preventive therapies less effective. In conclusion, this secondary analysis of two large, randomized, controlled trials suggests that IIT, with a goal of achieving normoglycemia, protects the renal function of critically ill patients.